A framework for stochastic scheduling of two-machine robotic rework cells with in-process inspection system. (October 2017) - Foumani, Mehdi; Smith-Miles, Kate; Gunawan, Indra; Moeini, Asghar
Highlights: Scheduling of two-machine robotic rework cells with in-process inspection scenario. Converting multiple-sensor systems into single-sensor systems. Deriving cycle times of two different cycles based on a geometric distribution. A mechanism of finding the maximum expected throughput for in-process inspection. Focusing on the domain of the problem for three various kinds of pickup scenarios. Abstract: This study is focused on the domain of a two-machine robotic cell scheduling problem for three various kinds of pickup scenarios: free, interval, and no-wait pickup scenarios. Particularly, we propose the first analytical method for minimizing the partial cycle time of such a cell with a PC-based automatic inspection system to make the problem more realistic. It is assumed that parts must be inspected in one of the production machines, and this may result in a rework process. The stochastic nature of the rework process prevents us from applying existing deterministic solution methods for the scheduling problem. This study aims to develop a framework for an in-line inspection of identical parts using multiple contact/non-contact sensors. Initially, we convert a multiple-sensor inspection system into a single-sensor inspection system. Then, the expected sequence times of two different cycles are derived based on a geometric distribution, and finally the maximum expected throughput is pursued for each individual case with free pickup scenario. Results are also extended for the interval and no-wait pick up scenarios as two well-solved classes of the scheduling problem. The waiting time of the part at each machine after finishing its operation is bounded within a fixed time interval in cells with interval pickup scenario, whereas the part is processed from the input conveyor to the output conveyor without any interruption on machines in cells with no-wait pickup scenario. We show a simple approach for solving these two scenarios of the problem which are common in practice.